1995
DOI: 10.1007/bf00290405
|View full text |Cite
|
Sign up to set email alerts
|

The spectra of base substitutions induced by the impCAB, mucAB and umuDC error-prone DNA repair operons differ following exposure to methyl methanesulfonate

Abstract: We have used the lacZ reversion assay to study the mutation spectra induced by the Escherichia coli chromosomal umuDC operon and of its two plasmid-borne analogues impCAB and mucAB following exposure of cells to UV light and methyl methanesulfonate (MMS). We have shown that the impCAB, mucAB and umuDC operons all produce a similar response to UV light which results almost exclusively in AT-->GC transitions. However, we found that the three operons produced different responses to alkylating agents. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Results from previous investigations have established that substitution of mucAB for umuDC can increase mutation frequencies induced by a wide range of mutagens and can change the spectrum of mutations detected (12,15,37). The rumAB operon has also been shown to enhance UV mutagenesis (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous investigations have established that substitution of mucAB for umuDC can increase mutation frequencies induced by a wide range of mutagens and can change the spectrum of mutations detected (12,15,37). The rumAB operon has also been shown to enhance UV mutagenesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Induced mutation frequencies are higher in strains expressing the muc and the rum operons rather than umuDC (4, 5, 23), an effect that has been ascribed in part to the greater susceptibility of MucA and RumA to proteolytic processing (20,23), although their relative ability to bind to a RecA-nucleoprotein filament also seems to be another mutagenically important phenotype (16,23). Different spectra of induced mutations have also been observed when mucAB has been substituted for umuDC (12,29). The increased mutability and changes in spectrum might arise, however, from a variety of causes.…”
mentioning
confidence: 99%
“…2 and 4). The lower activity of PolRI* expressed from the lac-promoter driven system compared to the native SOS-controlled operon in the case of AF-2, AFB1 and 1,8-DNP is probably due to its stoichiometric excess related to the other processive chromosomal DNA replicases competing for binding sites on the sliding clamp [25] or could be due to yet undiscovered third subunit of PolRI encoded on the pKM101 plasmid similarly to the case of the impCAB operon [4,35]. The optimal level of the PolRI catalytical subunit for different DNA adducts may be linked to its occupancy at the 3 binding sites on a β-subunit sliding clamp.…”
Section: In Detailmentioning
confidence: 99%
“…MMS is known to induce mutations mainly by formation of AP-sites as a result of the activity of the two 3-mA-DNA glycosylases recognising methylated purines in DNA (Friedberg et al, 1995). It has been reported that MMS-induced mutagenesis in E. coli is highly dependent on the level of UmuDC proteins (Doyle & Strike, 1995;Grzesiuk & Janion, 1996). Assuming that, in UV-induced mutagenesis of lO(am)8 phage, AP-sites might be the main premutagenic lesions we compared the effect of overproduction of UmuD' on MMS-and UV-induced mutagenesis of the phage.…”
Section: Different Effects Of Deficiency In Mismatch Repair On Mutagementioning
confidence: 99%